Seeking equivalence of the acute responses to continuous and interval aerobic exercise - Hughes, M. G.; Birdsey, L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
A diverse range of training protocols has previously been used to address the issue of how interval training adaptations differ to those obtained from continuous exercise. However, a weakness of these studies is that training duration, mean relative exercise intensity or both of these factors are not fixed at the same values during training. For this reason, it is difficult to be conclusive about the relative merits of these training types. In the present study we sought to identify which variation of a standard interval training protocol would elicit equivalent acute responses to a bout of continuous exercise using sessions of the same training duration. Methods: Nine healthy, active participants (mean VO2peak 44.5ml/kg/min) performed a maximal test, followed by four 42-min cycle ergometry bouts of either continuous (70 %VO2peak), or interval exercise. The three interval exercise sessions were variations of the methods used by Helgerud et al. (2007) and comprised six repetitions of 4min all at 85 %VO2peak, interspersed by 3 min of relative recovery at either low, medium or high intensities (45, 60 and 75% of VO2peak; i.e., LOW, MEDIUM, HIGH, respectively). Heart rate (HR), Oxygen consumption (VO2) and blood lactate concentration (BLa) were assessed through the four bouts. Results: The relative exercise intensities were different between sessions. Specifically, mean BLa was higher in all interval sessions and %VO2peak was lower in the continuous and LOW conditions than in the MEDIUM and HIGH conditions (74±3 and 70±4 %VO2peak vs. 77±4 and 83±4 %VO2peak, respectively). It was calculated that an interval-recovery intensity of 52 %VO2peak for both the mean VO2 and HR data would elicit the same mean response as continuous work at 70 %VO2peak. However, inspection of individual data showed a high variability of results, such that a recovery intensity of between 42 and 66 %VO2peak would elicit the same VO2 as the continuous bout in different individuals. The equivalent range for matching the HR responses was between 35 to 61 %VO2peak. Discussion: For the group mean data, adopting the interval training procedures used in the present study with a recovery intensity of around 52 %VO2peak should elicit equivalent mean VO2 and HR responses to continuous exercise at 70 %VO2peak. These findings may be useful for future studies where the physiological benefits of continuous vs. interval exercise are to be compared using matched duration and relative intensity. However, the extent of variation observed in the present study suggests that the individual responses to the contrasting exercise types should be considered if the acute physiological stresses in training are to be controlled for.